‘Rumi’ Networks of al-Sinkīlī: A Biography of Bāba Dāwud - Özay, Mehmet (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
This paper introduces Shaykh Dāwud ibn Ismā‘īl ibn Musṭafá Rūmī (also known as Bāba Dāwud or Musṭafá al-Rūmī) who was an Islamic scholar believed to have lived in Aceh sometime between 1650 and 1750 to the larger Muslim world. Shaykh Dāwud ibn Ismā‘īl ibn Musṭafá Rūmī is important for three reasons: (a) he lived during the time of the Sultanate of Aceh Darussalam (16th – 17th centuries) and he was the leading student and religious caliph of ‘Abd al-Ra’ūf al-Sinkīlī (Teungku Syiah Kuala), the well-known Acehnese religious scholar; (b) his Risālat masā’il al-muhtadī li ikhwān al-muhtadī has been taught at Islamic institutions in Aceh and all around the Malay world; and (c) no scholarly works have yet been written about him, despite the striking fact that he and Teungku Syiah Kuala co-founded the Dayah Manyang Leupue educational institution, to which he subsequently remained affiliated.DOI: 10.15408/sdi.v24i2.4441